EFFECTS OF SODIUM SILICATE, CALCIUM CARBONATE AND SILICIC ACID ON AMMONIUM NITRATE DEGRADATION AND ANALYTICAL INVESTIGATIONS OF THE DEGRADATION PROCESS ON AN INDUSTRIAL SCALE - Gezerman, Ahmet Ozan; Corbacioglu, Burcu Didem (ASSOC CHEMICAL ENG, 2015)
Ammonium nitrate is an inorganic chemical that has numerous applications in different industries. However, various problems are associated with both the production and subsequent storage of ammonium nitrate, including caking, degradation, unwanted phase transition, and recrystallization. Although several methods have been developed to attempt to solve these problems, many of them fail to work in practice. In this study, different compounds including silicic acid and sodium silicate were added to slow the progress of or to prevent the degradation of ammonium nitrate. Multiple instrumental analyses such as ion chromatography and scanning electron microscopy were used to monitor the degradation process.
Keywords: ammonium nitrate; caking; degradation; ion chromatography; downstream process; Chemistry; Engineering